Historical land use research on a study area of Cserhát mountains - Zagyvai, Gergely (JOURNAL OF LANDSCAPE ECOLOGY, 2008)
The paper presents the results of a historical landscape assessment focused mainly on the investigation on the land use changes in the area of Cserhát mountains during the two last centuries. The assessment has been based on historical maps, archive aerial photographs, archive statistical and literature data, local historical records and the opinions of local stakeholders. Common land cover categories of the first three historical map series and the topographical map of 1990s at the scale of 1:25000 were identified. In addition, we used other military maps and aerial photographs and statistics from the 20th century and assessed the main processes in land cover change. To the Naturalness and land use intensity value categories have been attached to each identified land cover categories. The definition of the values has been based on referenced literature, but adjusted also to local conditions. It has allowed to calculate indexes of the whole study area for the mentioned time period. Both the land use intensity and the naturalness index show the continuous, but different increase of pressures on landscape and at the same time its degradation in ecological conditions.